(untitled) (Tempo e Argumento, 2014)
This paper investigates the memory of bilateral relations produced by the U.S. Embassy in Brazil on the social network Flickr in the early months of the administration of the Democrat President Barack Obama. The set of images and texts in 19 posts made by the Embassy’s profile on the network in the first half of 2009 is analyzed here. It establishes connections between the production of memory, the U.S. political conjuncture, and U.S. political myths, such as Abraham Lincoln and John Kennedy. It also discusses ways of remembering and forgetting several events in bilateral relations throughout the 20th and 21st centuries, besides the positions published on the social network regarding Brazilian politics and history. Keywords: Social Networks; Flickr; President – United States.